I gave my baby tooth to science: Project Sunshine's role in the Limited Test Ban Treaty and cutting-edge pollution research. (2nd November 2021) - Alvarez, Robert; Mangano, Joseph
ABSTRACT: How many nuclear weapons can be detonated in support of weapons development or during a war before imperiling humans from radioactive fallout? That's the question the Atomic Energy Commission asked in the 1950s. To find the answer, scientists, citizens, and later the St. Louis Committee for Nuclear Information looked at baby teeth where strontium 90 – a radioactive isotope – is absorbed as if were calcium. The work combined scientific research with a political movement aimed at ending the nuclear arms race. It also played a role in the ratification of the 1963 Limited Test Ban Treaty. The wisdom and extraordinary effort of preserving these baby teeth for some 60 years opened doors for cutting-edge research involving an array of pollutants.